Activity of Daily Living of Elderly People in Rural Setting of Nepal: Situation and Scenarios in Present Context - Rai, Mahendra Kumar; Thapa, Naba Raj (Humanities and Social Sciences Journal, 2023)
Ageing is the global issue that affects almost all countries of the globe but its pace and level varies largely. The activities of daily living of elderly people are affected by various factors which reduce the activeness of elderly for their fullest contribution for development of society and nation. The activities of daily living are decreases with increasing the age and requires due medical care, support and treatment. The objective of this paper is to examine the contributing factors for activity of daily living in rural setting of Nepal. The cross-sectional study was carried out in Sunkoshi Rural Municipality, Sindhuli district in 2022 in which 413 elderly people aged 60+years were interviewed applying structured questionnaire. Chi-square test was employed to assess the association between dependent and independent variables whereas logistic regression was used to examine the contributing independent variables to activity of daily living. Of the total respondents, the significant proportion of respondents needed help for urination (50.12%) followed by carrying things (38.74%), walking (26.63%) and standing up (18.16%) whereas the least expressed that they need help for feeding (5.81%). Elderly having higher age have significantly higher likelihood of need of help for activity of daily living [70-79 years of age (OR=4.40, CI: 2.77-6.98) and 80+ years of age (OR=15.02, CI: 6.18-36.50)] than elderly aged 60-69 years of age. The likelihood of need of help for supporting daily activity is observed higher in joint family (OR=2.79, CI: 1.75-4.42) Janajati (OR=2.48, CI: 0.79-3.64) and having no provision of insurance (OR=2.88, CI: 0.97-8.55). The likelihood of need of help for daily activities is found higher among elderly who stopped working completely (OR=4.38, CI:1.46-3.34). The likelihood of seeking help for daily activity is significantly higher among elderly who do not involve in vigorous and moderate intensity activity and need of such help is observed highest among elderly who does not have capacity of grazing animals, putting grass and collecting dung. Daily activity of elderly people is the major symbol of active and successful ageing so it is most essential to promote the activity of daily living by ensuring and enhancing the aforementioned aspects.